Prove that tan(A+B+C) =(tan A + tan B tan C - tanAtanBtanC) ÷(1-tanAtanB-tanBtanC-tanAtanC)

Similar Questions
  1. Verify/prove that:(cotA+cotB)/(tanA+tanB)+(1-cotAcotB)/(1-tanAtanB) = 0
    1. answers icon 2 answers
  2. Now we prove Machin's formula using the tangent addition formula:tan(A+B)= tanA+tanB/1-tanAtanB. If A= arctan(120/119) and B=
    1. answers icon 2 answers
    1. answers icon 2 answers
  3. If it is given tan(A-B)tanA-tanB/-1+tanAtanB and tanP-1/1+tanP=tan195 Find the value of P
    1. answers icon 0 answers
more similar questions